(untitled) (Pravaha, 2018)
This Paper discusses city marketing in local governance in Nepalese perspectives and gives an overview of the city marketing technique and how it is used in various marketing research designed and applications. A basic outline of how the technique works and its criteria, including its main assumptions are discussed as well as when it should be used in various geographical locations. City marketing is promoted to enlighten readers on how place marketing strategies works, an example of how to run city marketing on municipalities is provided. This will allow readers to develop a better understanding of when to employ city marketing and how to interpret the role of city marketing in the output. By keeping a view of this reality, this study tries to identify the difference between city marketing in local governance on the basis of gender and household size of Changunarayan and Suryabinayak municipalities. Pravaha Vol. 24, No. 1, 2018, page: 175-180